A Critical Analysis of Social Responsibility Practices in Alcohol Advertising Campaigns (Issues in Social and Environmental Accounting (ISEA), 2015)
Culture plays a role in creating young alcoholics and has been at the center of debates about the impact of alcohol advertising on patterns of consumption. This research addressed the impact of alcohol advertising on local culture and its social implications in a developing economy. Stakeholders, including young people and marketing representatives from an alcohol producer in Country X, were examined to determine their perspectives of the use of alcohol advertising strategies. The findings were consistent with previous academic research and expectancy     theory that indicate alcohol advertising can influence the normative behavior of young persons and their attitudes toward the use of alcohol. That is, alcohol producers can only claim to be socially responsible if their marketing strategies considers the concerns of the wider           community. The Country X alcohol producer in this study, this claim requires organizational change to make the company more closely aligned to industry best practices.